IMPACT OF SOCIO-ECONOMIC PROCESSES ON THE DEVELOPMENT OF RAINIS PARK IN LIEPAJA UNTIL WORLD WAR II - Ozola, Silvija (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2019)
In the 19th century, a special attention was devoted to arrangement of Libava urban environment. Public gardens were created. At the beginning of mass culture, a new urban landscape conception got into focus of artistic attention. In the Republic of Latvia, physically and mentally competent living environment for a person developed. Green urban structures were improved. Public activities in Rainis Park were expanded. The object of the research – Rainis Park's functional and visual changes in Liepaja. Research problem – Rainis Park's architectural spatial and functional changes caused by sociopolitical processes have not been sufficiently studied. Research novelty – Rainis Park's spatial and functional structure is analyzed in the context of city development. The goal of the research – to determine the most typical changes in Rainis Park's historical plan and visual image. Main methods applied – this study is based on analysis of archive documents, projects and cartographic materials of urban planning, as well as study of published literature and inspection of buildings in nature.